Biliary decompression promotes Kupffer cell recovery in obstructive jaundice. Issue 6 (June 1996) - Clements, W D; McCaigue, M; Erwin, P; Halliday, I; Rowlands, B J
Abstract : BACKGROUND: Jaundiced patients undergoing surgical procedures have an increased risk of Gram negative sepsis with potential morbidity and mortality. Depressed Kupffer cell clearance capacity (KCCC) predisposes jaundiced patients to endotoxaemia and its sequelae. Biliary decompression remains the main therapeutic strategy in obstructive jaundice. AIMS: This study investigates the efficacy of internal (ID) and external biliary drainage (ED) on KCCC in an experimental model of extrahepatic biliary obstruction. METHODS: Adult male Wistar rats (250-300 g) were assigned to one of six groups: sham operated, where the bile duct was mobilised but not divided; bile duct ligation (BDL) for three weeks, and sham operated or BDL for three weeks followed by a second laparotomy and further 21 days of ID or ED, by way of choledochoduodenostomy or choledochovesical fistula respectively. KCCC was measured using an isolated hepatic perfusion technique with FITC labelled latex particles (0.75 mu) as the test probe. Plasma was assayed for bilirubin, endotoxin, and anticore glycolipid antibody (ACGA) concentrations. RESULTS: Jaundiced rats had reduced KCCC (p < 0.001), increased concentrations of ACGA (p < 0.001), and endotoxin (p < 0.001) compared with controls. Biliary drainage for three weeks produced a recovery in KCCC and normalisation of endotoxin and ACGA concentrations, however, external drainage was less effective than ID (p < 0.01). CONCLUSIONS: These data support the hypothesis that endotoxaemia and its mediated effects are integral in the pathophysiology of jaundice. Furthermore, a short period of internal biliary drainage is a useful therapeutic strategy in restoring Kupffer cell function and negating systemic endotoxaemia and consequent complications in biliary obstruction.